The beginning of the Primary Care Social Services in Aragon - Matías-Solanilla, Antonio (Acciones e Investigaciones Sociales, 2019)
The Primary Care Social Services in Aragon were first set up in Zaragoza in 1980 and a few years later they also opened up in various towns in the three Aragonese provinces. On the occasion of the fortieth anniversary of the first experiences, it is imperative to recall what these beginnings were like and try to see them in the context of those times. With this in mind, a bibliographical search and analysis was conducted both with respect to the various legal provisions and also for the first reports published on these services.Likewise, it is also necessary to point out and recognise the role played by the social workers as, in most cases, it always turned out to be women at the head of these services right from the outset.
Keywords: primary care social services; social policy; Aragon; social workers